Nutritional Viewpoints on Eggs and Cholesterol - Michihiro Sugano; Ryosuke Matsuoka (Foods, 2021)
Although most current epidemiologic studies indicate no significant association between consuming one egg daily and blood cholesterol levels and cardiovascular risk, arguments still persist with a positive association. Since the diet is one of the most influential factors for this association, we illustrate characteristic features in Japanese people whose dietary pattern is distinct from that, for example, the US (United States) population. Available epidemiologic studies in healthy Japanese people show no association between consumption of one egg daily and blood cholesterol level, consistent with those observed in the US population. However, when consumption of major nutrients and food sources of cholesterol are compared to the US population, Japanese people may have an extra-reserve against the influence of eggs on cardiovascular risk markers, despite consuming relatively more eggs. Further discussion on the influence of nutrients contained in the egg and dietary pattern, including interaction with gut microbes, is necessary. In addition, special consideration at the personalized level is needed for judgment regarding dietary cholesterol not only for hypercholesterolemic patients but for hyper-responsive healthy persons. Although randomized controlled trials with long-term follow-up are required to evaluate the association between consumption of eggs and human health, available information, at least from the nutritional viewpoint, suggests that egg is a healthy and cost-efficient food worldwide.